2023
DOI: 10.1007/s00167-023-07418-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic OA, bone marrow lesions, higher body mass index and medial meniscal root tears are significantly associated with medial meniscus extrusion with OA or medial meniscal tears: a systematic review and meta-analysis

Abstract: PurposeMedial meniscus extrusion (MME) refers to the protrusion of the medial meniscus beyond the tibial edge by more than 3 mm, leading to a deficiency of the hoop strain. MME commonly occurs in conjunction with osteoarthritis (OA) or medial meniscal tears (MMT). However, factors associated with concomitant MME in patients with OA or MMT have not been systematically reviewed. This study aims to perform a systematic review and meta‐analysis to identify factors associated with concomitant MME in OA or MMT. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In the knee, both menisci complement and protect the osteochondral unit [ 25 ]. Meniscus injury is common [ 20 , 32 ], and meniscus tissue insufficiency and loss are one of the most important causes of knee OA [ 5 7 , 21 , 49 , 52 ]. The principle of inducing a defined meniscal lesion is applied in many animal models to model OA initiation and development [ 42 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the knee, both menisci complement and protect the osteochondral unit [ 25 ]. Meniscus injury is common [ 20 , 32 ], and meniscus tissue insufficiency and loss are one of the most important causes of knee OA [ 5 7 , 21 , 49 , 52 ]. The principle of inducing a defined meniscal lesion is applied in many animal models to model OA initiation and development [ 42 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies have demonstrated that the medial meniscus transmits 50% of the joint load in the medial compartment and that at least 50% of the compressive load of the knee joint is transmitted through the meniscus in extension [1,2]. As a consequence of a MME, the reduced tibiofemoral contact area increases mean and peak weight-bearing forces resulting in a diverged knee kinematic and ultimately leading to an increased risk of osteophytosis, chondral lesions, loss of cartilage, and eventually osteoarthritis (OA) [3][4][5][6][7][8][9].…”
Section: Extended Author Information Available On the Last Page Of Th...mentioning
confidence: 99%
“…MME frequently occurs in conjunction with radial medial meniscus tears (MMT), with an incidence of 46.7%, particularly in medial meniscus root tears (MMRT), up to 83.3% of cases [4].…”
Section: Extended Author Information Available On the Last Page Of Th...mentioning
confidence: 99%
“…A medial meniscus posterior root tear (MMPRT) is an injury to the posterior meniscal attachment of the tibia that causes abnormal knee joint kinematics. MMPRTs disrupt the hoop function and cause medial meniscus extrusion (MME) [9,25,31,34]. Conservative treatment of MMPRTs is not always efective, and meniscal repair is more efective than both partial meniscectomy and conservative treatment [4,21,22,24].…”
Section: Introductionmentioning
confidence: 99%